2015
DOI: 10.1038/cddis.2014.557
|View full text |Cite
|
Sign up to set email alerts
|

Stromal SLIT2 impacts on pancreatic cancer-associated neural remodeling

Abstract: Pancreatic ductal adenocarcinoma (PDA) is a critical health issue in the field of cancer, with few therapeutic options. Evidence supports an implication of the intratumoral microenvironment (stroma) on PDA progression. However, its contribution to the role of neuroplastic changes within the pathophysiology and clinical course of PDA, through tumor recurrence and neuropathic pain, remains unknown, neglecting a putative, therapeutic window. Here, we report that the intratumoral microenvironment is a mediator of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 39 publications
1
54
0
Order By: Relevance
“…2G). Altogether, these data revealed that while numerous cell types within PDA potentially express LIF, the ability to secrete it seems restricted to the stromal compartment and in particular mostly to activated fibroblasts, a major cell component of PDA microenvironment that we have recently linked to PANR (12).…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…2G). Altogether, these data revealed that while numerous cell types within PDA potentially express LIF, the ability to secrete it seems restricted to the stromal compartment and in particular mostly to activated fibroblasts, a major cell component of PDA microenvironment that we have recently linked to PANR (12).…”
Section: Resultsmentioning
confidence: 98%
“…We previously showed that the stromal compartment can, through its secretory ability, impact nerve system reorganization within PDA tumors (12). Regarding recent studies revealing a role of inflammatory processes in PANR (11,22), we hypothesized that some genes/pathways, involved in the regulation of inflammatory processes, may be upregulated in the stromal compartment of pancreatic cancer and could impact PANR.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations